Babymouse : burns rubber! - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2010)
Babymouse's dreams of being a race car driver come true when she and her best friend Wilson enter a soap box derby.
Keywords: Animals -- Fiction; Graphic novels; Humorous stories; Imagination -- Fiction; Mice -- Fiction; Soap box derbies -- Fiction; Graphic novels